AFIKSASI BAHASA MELAYU RIAU ISOLEK SERAPUNG - Rusniarti Rusniarti; Charlina Charlina; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research titled Malay Language Affixation Riau Isolek Serapung. This study aims to identify data on affixes, namely (1) type, (2) function and (3) its meaning. The type of research used is qualitative research. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words of the people and the behavior observed for the research. Sources of data in this study are informers or native speakers from Malay in Serapung Village, Kuala Kampar Subdistrict, Riau Province. Data collection techniques in this study include recording, interviewing and referring to notes and notes from reports. The technique of data analysis is done by listening, transcribing, describing and concluding a report. Based on research found 5 affix consisting of prefix, infix, suffix, confix and simulfiks. The details of the data are (1) the type of affix 5, ie prefix, infix, suffix, confix and simulfiks, (2) affix function and (3) meaning.Keywords: Affixes, Affixes And Affixes.